Poverty, inequality, and spillover in Mexico's education, health, and nutrition program - Handa, Sudhanshu; Huerta, Mari-Carmen; Perez, Raul; Straffon, Beatriz (International Food Policy Research Institute, 2000)
This report provides an evaluation of the community level effects of PROGRESA using household level data from various rounds of PROGRESA's evaluation sample (the ENCEL surveys). These surveys, along with ENCASEH 1997, provide a valuable source of information on household and community level characteristics before and after the implementation of the program. Other reports in the evaluation series have focused on the direct effects of PROGRESA, using the control and treatment groups in the ENCELS. The objective of this report is slightly different, in that it explores the possible spill-over effects of the program on the wider community. Hence instead of focusing on program effects at the individual level, we focus on aggregate community level indicators of well-being such as poverty, inequality, and school and health care attendance rates, in order to assess the impact of PROGRESA at this level. Using the data sets mentioned above, we develop five indicators with which to measure the potential impact of PROGRESA at the community level. These indicators are: 1) changes in rates of relative poverty, 2) changes in inequality, 3) school continuation rates, 4) changes in nutrition surveillance rates, 5) changes in prices (inflation). Exploiting the longitudinal aspect of the evaluation data, we construct "difference in differences" estimators and use regression techniques to isolate community level program effects.